PREPARATION OF POROUS TITANIA AEROGEL BY CO2 SUPERCRITICAL EXTRACTION TECHNIQUE. - Silvester Tursiloadi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2004)
PREPARATION OF POROUS TITANIA AEROGEL BY CO2 SUPERCRITICAL EXTRACTION TECHNIQUE. Porous anatase titania that is attractive to its notable functions for photo catalysis and photon-electron transfer. A method for producing the porous anatase titania at low temperature is with dissolving of a titanium alkoxide in a methanol to give a titanium alkoxide solution, adding a mixed solution containing water, nitric acid catalyst and a methanol to the titanium alkoxide solution to perform hydrolysis and simultaneous polymerization to give a polymer solution (gel). The solvent in wet gels was super-critically extracted in CO2 at 60°C and 22 Mpa. Thermal evolution ofthe microstructure ofthe gels were evaluated by TGA—DTA, N2 adsorption, TEM and XRD. A porous titania, which has an anatase-form crystalline structure, an anatase-form particle diameter about 4 nm, average pore diameter of 13 nm, a BET specific surface area of 195 m2/g and a total pore volume of 0.55 cm2/g was obtained as prepared condition. The transformation of anatase phase to rutile phase occurred at 600 °C.